Cry havoc : a thriller [compact disc, unabridged] - Carr, Jack (Joint pseudonym) (Tom Reece, 2025)
1968. A time of division. A time of civil unrest. A time of war. Just before the Tet Offensive changes the dynamic in Vietnam, before President Johnson announces he will not run for reelection, before the assassinations of Martin Luther King, Jr. and Bobby Kennedy, as riots and protests rage across the nation, a spy ship, the USS Pueblo, is captured by communist forces off the coast of North Korea. The crew thought they had destroyed everything of intelligence value. They were wrong. As a KGB 'illegal' elicits information from a high-ranking CIA official, and teams of special operators infiltrating into Laos, Cambodia, and North Vietnam disappear without a trace, an ambitious Soviet advisor launches an ingenious plan with consequences that reach far beyond the battlefields of Southeast Asia, one that will forever alter the world balance of power. Tom Reece, a SEAL operator attached to the highly classified and shadowy MACV-SOG is about to be thrust into a bloody battle to discover the truth. From the Kremlin to the White House, from the streets of Saigon to the rugged A Shau Valley, along the paths of Ho Chi Minh Trail and into the secret war in Laos, Navy SEAL Tom Reece has an official mission assigned by Military Assistance Command, Vietnam-Studies and Observations Group, but it's his unofficial mission that might get him killed.